2020
DOI: 10.1093/brain/awaa096
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional gut-to-brain and brain-to-gut propagation of synucleinopathy in non-human primates

Abstract: Abstract In Parkinson’s disease, synucleinopathy is hypothesized to spread from the enteric nervous system, via the vagus nerve, to the CNS. Here, we compare, in baboon monkeys, the pathological consequences of either intrastriatal or enteric injection of α-synuclein-containing Lewy body extracts from patients with Parkinson’s disease. This study shows that patient-derived α-synuclein aggregates are able to induce nigrostriatal lesions and enteric nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
136
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 28 publications
5
136
1
7
Order By: Relevance
“…[2][3][4][5][6] This "brain-first"/"body-first" division is supported primarily by animal models demonstrating bidirectional extension between the gut and the brain of alpha-synuclein pathology along sympathetic and parasympathetic pathways. 6,7 This most recent study by Horsager and colleagues suggests that some patients exhibit significantly more peripheral organ pathology at the time of initial assessment than others. Although the subtype hypothesis was not proposed as a panacea to explain all of the clinical and pathological variability of PD, there is need for a critical appraisal of its validity and utility in explaining the heterogeneity and individual complexity of PD and informing the direction of future research.…”
mentioning
confidence: 98%
“…[2][3][4][5][6] This "brain-first"/"body-first" division is supported primarily by animal models demonstrating bidirectional extension between the gut and the brain of alpha-synuclein pathology along sympathetic and parasympathetic pathways. 6,7 This most recent study by Horsager and colleagues suggests that some patients exhibit significantly more peripheral organ pathology at the time of initial assessment than others. Although the subtype hypothesis was not proposed as a panacea to explain all of the clinical and pathological variability of PD, there is need for a critical appraisal of its validity and utility in explaining the heterogeneity and individual complexity of PD and informing the direction of future research.…”
mentioning
confidence: 98%
“…However, studies by one group found that the pathology failed to progress past the dorsal motor nucleus (149,150). Another group injected baboons with patient-derived Lewy body extracts and found that pathology spread to the central nervous system through circulation rather than via the vagus nerve (151). Regardless, there is mounting evidence indicating that bacterial amyloids such as curli, present at high levels in biofilms in the gut, are capable of cross-seeding αSyn aggregation and that αSyn aggregates are capable of spreading from the gut to the brain as a possible initiating event in PD (112,127,134,139,(146)(147)(148)151).…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…The levels of a-syn in the blood of baboons injected were increased, which was positively correlated with the levels of a-syn in ENS. Endogenous a-syn may be transmitted long-distance and bidirectional between ENS and the brain through the circulatory system (Arotcarena et al, 2020).…”
Section: Microbiota-targeted Intervention Strategies To Manage Pdmentioning
confidence: 99%